2022
DOI: 10.1021/acs.nanolett.1c04786
|View full text |Cite
|
Sign up to set email alerts
|

Field-Free Spin–Orbit Torque Switching Enabled by the Interlayer Dzyaloshinskii–Moriya Interaction

Abstract: Perpendicularly magnetized structures that are switchable using a spin current under field-free conditions can potentially be applied in spin−orbit torque magnetic randomaccess memory (SOT-MRAM). Several structures have been developed; however, new structures with a simple stack structure and MRAM compatibility are urgently needed. Herein, a typical structure in a perpendicular spin-transfer torque MRAM, the Pt/ Co multilayer and its synthetic antiferromagnetic counterpart with perpendicular magnetic anisotrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
(100 reference statements)
0
26
1
Order By: Relevance
“…Though the exact mechanism of this observed field-free SOT switching is unclear at present, the Dzyaloshinskii-Moriya interaction (DMI) should play an important role, because both the large difference in interfacial DMI of bottom and top magnetic layers and the additional interlayer DMI can lead to field-free SOT switching in SAFs. [38,39] An in-depth investigation is highly desired and the performance of field-free SOT switching can be further improved via some common approaches, such as exchange bias, interlayer exchange coupling, and tilted sputtering. [36,40,41] Finally, the SOT switching behavior of Type IV (Figure S4b, Supporting Information) is very similar to that of Type I.…”
Section: Magnetization Switching By Sotmentioning
confidence: 99%
“…Though the exact mechanism of this observed field-free SOT switching is unclear at present, the Dzyaloshinskii-Moriya interaction (DMI) should play an important role, because both the large difference in interfacial DMI of bottom and top magnetic layers and the additional interlayer DMI can lead to field-free SOT switching in SAFs. [38,39] An in-depth investigation is highly desired and the performance of field-free SOT switching can be further improved via some common approaches, such as exchange bias, interlayer exchange coupling, and tilted sputtering. [36,40,41] Finally, the SOT switching behavior of Type IV (Figure S4b, Supporting Information) is very similar to that of Type I.…”
Section: Magnetization Switching By Sotmentioning
confidence: 99%
“…[24,25] Besides, some works reveal that IL-DMI is promising to facilitate field-free switching in spin orbit torque (SOT)-driven memory applications. [26,27] To further pave a wide pathway of spintronic devices applications utilizing IL-DMI, it is desirable to investigate the properties of IL-DMI and manipulate the IL-DMI.…”
Section: Introductionmentioning
confidence: 99%
“…Another route toward Hopfions is offered by the antisymmetric interlayer exchange interaction, which has been termed as RKKY-DMI or interlayer DMI (IL-DMI). It favors spin canting between layers in the lateral direction and originates from in-plane symmetry breaking. This allows for a highly sought-after tuning mechanism for 3D magnetic textures, which could stabilize such structures in magnetic multilayers without confinement.…”
mentioning
confidence: 99%
“…This would allow for writing and deleting operations, which are necessary when the different magnetic textures are employed as bits. Furthermore, the IL-DMI can allow for field-free switching as recent studies have shown. , This pure electrical switching facilitated by the IL-DMI offers new possibilities for spintronic devices while the IL-DMI is relatively simply induced by an oblique sputtering technique or a magnetic field during deposition . Conventionally, the strength of both DMI and IL-DMI is set during sample growth.…”
mentioning
confidence: 99%
See 1 more Smart Citation